2002
DOI: 10.4049/jimmunol.169.4.2134
|View full text |Cite
|
Sign up to set email alerts
|

Ras Activation in T Cells Determines the Development of Antigen-Induced Airway Hyperresponsiveness and Eosinophilic Inflammation

Abstract: The central role for Th2 cells in the development of Ag-induced airway hyperresponsiveness and eosinophilic inflammation is well documented. We have reported a crucial role for TCR-induced activation of the Ras/extracellular signal-regulated kinase mitogen-activated protein kinase cascade in Th2 cell differentiation. Here, we show that the development of both OVA-induced airway hyperresponsiveness and eosinophilic airway inflammation in a mouse asthma model are attenuated in transgenic mice by the overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…In our previous reports, we showed that Th2 cell differentiation and Th2-dependent airway inflammation are highly dependent on the TCR-mediated activation of the Ras-ERK MAPK cascade (6,48). In the present study, we detected significantly reduced activation of the Ras/MAPK cascade in aging mouse CD4 ϩ T cells (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In our previous reports, we showed that Th2 cell differentiation and Th2-dependent airway inflammation are highly dependent on the TCR-mediated activation of the Ras-ERK MAPK cascade (6,48). In the present study, we detected significantly reduced activation of the Ras/MAPK cascade in aging mouse CD4 ϩ T cells (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…We reported that Th2 responses are highly dependent on the extent of activation of the Ras-ERK MAPK cascade (6,48). The hyperacetylation of histones associated with the Th2 cytokine gene locus is dependent on the expression of GATA3 (43,46).…”
Section: Chromatin Remodeling Of the Th2 Cytokine Gene Locus In Cd4 ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…A modest (Ϸ2-fold) but reproducible increase in the number of eosinophils was detected in mice treated with OVA alone as compared with those in PBS-or LPS-treated mice. The extent of eosinophilic infiltration induced in this protocol was significantly lower than that induced by intraperitoneal immunization of OVA with alum (data not shown) (28,29). However, the numbers of total cells and eosinophils were significantly increased when wild-type ϩ͞ϩ mice were treated with both OVA and LPS.…”
mentioning
confidence: 74%
“…In this respect, MIF's ability to induce sustained ERK-1͞2 activation may be of importance (18). Activation of the ERK-1/2 mitogen-activated protein kinase (MAPK) cascade in the differentiation of T H 2 cells may be necessary for antigen-induced airway hyperreactivity and eosinophilic inflammation (38).…”
Section: Discussionmentioning
confidence: 99%